The direct cost of treating diabetic foot And its associated factors in the Orthopaedic wards, Hospital Universiti Sains Malaysia (HUSM), Kota Bharu, Kelantan - Dollar, Zawiyah (2007)
INTRODUCTION: Diabetic foot is one of the devastating complications of diabetes mellitus. The cost of treating it is increasing as its prevalence is increased. Therefore, the aim of this study was to estimate the direct cost incurred by health care provider in treating diabetic foot and its associated factors in the Orthopaedic Wards, Hospital Universiti Sains Malaysia (HUSM), Kota Bharu, Kelantan. METHOD: A cost of illness study was done prospectively whereby 1 01 diabetic foot patients who were admitted to the Orthopaedic wards 4 Utara and 4 Selatan, HUSM from 1st May to 31st December 2005 were purposely selected. The subjects underwent face-to-face interview and their medical records were reviewed. The macrocosting and microcosting were performed on each of the patient. The cost of treating diabetic foot was divided into capital and recurrent costs. The mean cost per patient per admission was calculated. Multiple linear regression analysis was used in determining the socio-demographic and clinical characteristic factors associated with the cost. RESULT: Majority of the subjects were Malay (97.1 %) and the others were Chinese. Female (51.5%) was predominant than male (48.5%). The mean (SD) age (years) of the subjects, duration of having diabetes (years) and length of hospitalization (days) was 56.2(9.78), 10.7(6.41) andl3.2 (4.68), respectively. The mean (SD) direct cost per patient per admission was Ringgit Malaysia (RM) 11,763.88 (6,843.96). The mean (SD) for capital. and recurrent cost was RM 53.51(32.83) and RM11,710.37 (6,813.24) respectively. Amputation, debridement, fever at presentation, presence of hypertension and attendance of split skin grafting were significantly associated with the cost by multiple linear regression analysis. CONCLUSION: The mean direct cost per patient per admission of treating diabetic foot was RM 11,763.88, which mostly contributed by recurrent cost and was associated with the presence of hypertension as co-morbidity, patient who presented with fever and surgical procedure performed which was split skin grafting, amputation or debridement. Hence, strategies in preventing the lesion and its severity need to be strengthened and improvement in the management of diabetes mellitus and its chronic complications can reduce the length of hospitalization and its economic burden.